Método para detecção do ONSET da atividade muscular para medida do limiar do reflexo de estiramento tônico - Silva, Andrei Nakagawa (2015)
Spasticity isamotordisorderthatmightbecausedbystroke,spinalcordinjury, multiplesclerosisandcerebralpalsy,forexample.Itischaracterizedbyanincreaseof velocity-dependenttonicstretchreflex,causedbythehiperexcitabilityofthestretchre- flex.Thecorrectassessmentofspasticityisessentialtoclinicalpractice,helpinginthe proposal ofrehabilitationtherapiesthatarebettersuitedandtrackingofthepatient s condition moreaccurately.Inthiscontext,anewmethodhasbeenfoundinthelitera- ture basedonthemeasurementoftheTonicStretchReflexThreshold(TSRT).Thisisa more interestingalternativethantheothers,consideringthatisarepresentationofthe excitabilityofspinalcircuitsratherthanameasurementofthespasticlimbresistance feltduringapassivestretch.Bystudyingtheproposedmethodology,somepointswere foundthatcouldchangetheTSRTvalue,influencingtheoutcomeoftheclinicalasses- sment. Thedetectionoftheonsetofmuscularactivityintheelectromyographicsignal (EMG) isoneofthem.Thus,theobjectiveofthisworkwastoaddresstheprecision of differentEMGonsetdetectionmethodsthathasbeenusedformeasuringtheTSRT and checkhowtheywouldinterferewiththespasticityassessmentwhenappliedto real experimentalsignals.TheresultspresentedsuggeststhattheTSRTisdirected influenced bytheEMGonsetdetectionmethod.Furthermore,theonesthataremore precise,arelikelytoproducebetterresultswithregressionlinesthataremorelinear and, consequently,validTSRTvalues.